Addition of Chromium (Cr+3) in the diets containing fermented yellow corn meal on jelawat, Leptobarbus hoevenii - HENDRY YANTO; JUNIANTO JUNIANTO; RITA ROSTIKA; YULI ANDRIANI; ISKANDAR ISKANDAR (Smujo International, 2017)
Yanto H, Junianto, Rostika R, Andriani Y, Iskandar. 2017. Addition of Chromium (Cr+3) in the diets containing fermented yellow corn meal on jelawat, Leptobarbus hoevenii. Nusantara Bioscience 9: 214-219. This experiment aimed to find the optimal level of Cr+3 in the diets containing fermented yellow corn meal to increase the growth of jelawat (Leptobarbus hoevenii Bleeker, 1851). The completely randomized design had five levels of Cr+3, they were A0 (0.52), A1 (1.55), A2 (3.03), A3 (4.52) and A4 (6.04) mg kg-1 in the diet. The source of Cr+3 was CrCl3 6H2O which was fermented by Saccharomyces cerevisiae. The results showed that Cr+3 in diets could activate the insulin and regulate the blood glucose. The fastest increase in blood glucose occurs 5 hours after feeding on Chromium 1.5 mg kg-1. The liver and muscle glycogen, protein and lipid of bodies, protein and lipid retentions, daily growth rate, and feed efficiency were significant (P<0.05). The diet containing Cr+3 1.55 mg kg-1 resulted in the highest for liver glycogen, body protein, body lipid, protein and lipid retentions, daily growth rate and feed efficiency. The Cr+3 level of 1.55 mg kg-1 in the diet contained 30% fermented yellow corn meal and 42.79% total carbohydrate was the best for the growth and feed efficiency of jelawat.